Analgesic effects of a novel pH-dependent μ-opioid receptor agonist in models of neuropathic and abdominal pain. Issue 11 (November 2018) - Rodriguez-Gaztelumendi, Antonio; Spahn, Viola; Labuz, Dominika; Machelska, Halina; Stein, Christoph
Abstract : Abstract: Recently, (±)- N -(3-fluoro-1-phenethylpiperidine-4-yl)- N -phenyl propionamide (NFEPP), a newly designed μ-opioid receptor (MOR) agonist with a low pKa, has been shown to produce injury-restricted analgesia in models of inflammatory and postoperative pain, without exhibiting typical opioid side effects. Here, we investigated MOR binding of NFEPP in brain and dorsal root ganglia, pH in injured tissues, and the analgesic efficacy of NFEPP compared with fentanyl in a chronic constriction injury model of neuropathic pain, and in the acetic acid–induced abdominal writhing assay in rats. Binding experiments revealed significantly lower affinity of NFEPP compared with fentanyl at pH 7.4. In vivo, pH significantly dropped both at injured nerves after chronic constriction injury and in the abdominal cavity after acetic acid administration. Intravenous NFEPP as well as fentanyl dose-dependently diminished neuropathy-induced mechanical and heat hypersensitivity, and acetic acid–induced abdominal constrictions. In both models, NFEPP-induced analgesia was fully reversed by naloxone methiodide, a peripherally restricted opioid receptor antagonist, injected at the nerve injury site or into the abdominal cavity. Our results indicate that NFEPP exerts peripheral opioid receptor–mediated analgesia exclusively in damaged tissue in models of neuropathic and abdominal pain. Abstract : Supplemental Digital Content is Available in the Text.The newly designed, pH-dependent opioid agonist NFEPP induced analgesia exclusively through peripheral opioid receptors in models of neuropathic and abdominal pain.